The Dilemma of Communicative Action and Rational Strategy in Water Governance; Qualitative Research of the Communicative Process of Water Stakeholders in Rafsenjan Plain - SeyedehBahar ‌‌Zandrazavi; Hadi Khaniki; Daryoush Boostani; Akbar Nasrolahi (Dānishhā-yi būmī-i Īrān, 2019)
The government has not succeeded in governing the common pool resources. As a result, some groups are searching for their answers in privatization management and others believe in participatory management. This research compares the communicative approaches of stakeholders regarding the groundwater sustainability in Rafsenjan plain. The research methodology was grounded theory (GT). Participants were chosen through snowball sampling and theoretical saturation to maximize variation sampling. Focus group discussions were conductedamong a total of 115 people in ten stakeholders’ groups. Each sub-group consisted of 10 to 15 members. The researchers learned about two different approaches among water stakeholders. Those groups being interested in communicative action have seen the reasons for the water instability as "lack of civil society in water law regulation", "water-based employment policies". They insisted on strategies like "participation", "fairness" and "accountability"for a way out. In contrast, the other group found the reasons for the water instability in "energy subsidy", "farmers' lack of technical awareness" and " vague water rules" and their proposal is the "water's market" and "extension". These two different approaches derive from two different perceptions’ "participatory" and "rational strategy". As a result,they had a different attitude toward groundwater management and sustainability